Is Private Saving in Latin America and the Caribbean Different?. Issue 4 (24th January 2017) - Grigoli, Francesco; Herman, Alexander; Schmidt‐Hebbel, Klaus
Abstract: Private saving and economic growth are intimately linked, and low saving rates in Latin America and the Caribbean (LAC) have often been held responsible for disappointing growth in the region. Thus, identifying factors that spur saving is critical. This paper surveys previous empirical studies on LAC, highlighting contradictions, omissions and in some cases inconclusiveness of findings. Relying on a large dataset and a nested econometric framework, it analyzes private saving patterns and explores the role of its determinants in LAC, across LAC sub‐regions and compared with other regions. While the results highlight great heterogeneity in private saving rates within LAC and compared with the rest of the world, saving determinants are broadly the same notwithstanding some differences in sensitivity and contributions' sizes, and include its lag, income, demographics and public saving.